2017
DOI: 10.1038/nature21689
|View full text |Cite
|
Sign up to set email alerts
|

A B12-dependent radical SAM enzyme involved in oxetanocin A biosynthesis

Abstract: Summary Oxetanocin-A (OXT-A, 1) is a potent antitumor, antiviral, and antibacterial compound. Biosynthesis of OXT-A has been linked to a plasmid-borne, Bacillus megaterium gene cluster that contains four genes, oxsA, oxsB, oxrA, and oxrB. Here, we show that the oxsA and oxsB genes are both required for the production of OXT-A. Biochemical analysis of the encoded proteins, a cobalamin (Cbl)-dependent S-adenosylmethionine (AdoMet) radical enzyme, OxsB, and an HD-domain phosphohydrolase, OxsA, revealed that OXT-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
211
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(221 citation statements)
references
References 57 publications
10
211
0
Order By: Relevance
“…9,11,21 This hypothesis is consistent with the only known crystal structure of a Cbl-dependent radical SAM enzyme, OxsB. 25 Though not a RSMT, the substrate binding site of OxsB is postulated to be interposed equidistant between the C5′ of SAM and the Co of the Cbl cofactor.…”
supporting
confidence: 75%
“…9,11,21 This hypothesis is consistent with the only known crystal structure of a Cbl-dependent radical SAM enzyme, OxsB. 25 Though not a RSMT, the substrate binding site of OxsB is postulated to be interposed equidistant between the C5′ of SAM and the Co of the Cbl cofactor.…”
supporting
confidence: 75%
“…80 A structurally homologous N-terminal domain is also found in B 12 -dependent radical SAM enzymes where it binds the cobalamin cofactor. 81 While most functionally characterized members of this group so far are responsible for methylation of unactivated carbon or phosphorus centers, recent studies have revealed that some of these enzymes are responsible for carbon skeleton formations where the roles of B 12 or the N-terminal domain itself are still unclear. Using the representative members, NikJ/PolH, OxsB and BchE, we will discuss the mechanism of C–C bond formation in this family.…”
Section: Radical Sam Enzymes With N-terminal Cofactor Binding Domainsmentioning
confidence: 99%
“…20a). 81 Both of these genes have been heterologously expressed and characterized. Recombinant OxsA was shown to catalyze hydrolysis of phosphorylated OXT-A compounds.…”
Section: Radical Sam Enzymes With N-terminal Cofactor Binding Domainsmentioning
confidence: 99%
See 2 more Smart Citations